A Framework for Durability Design with Strain-Hardening Cement-Based Composites (SHCC) State-of-the-Art Report of the RILEM Technical Committee 240-FDS - van Zijl, Gideon P.A.G; Slowik, Volker (RILEM State-of-the-Art Reports, 2017)
This book captures the state of the art of the durability of fibre-reinforced strain-hardening cement-based composites (SHCC) and the durability of structures or structural elements manufactured in full or in part with this class of modern construction materials. Highlights include: -       Reflection on durability performance of existing applications in patch repair, a water reservoir and highway bridges. -       Guidelines for tensile testing towards durability assessment of cracked SHCC. -       New crack pattern related ingress rate indices for water and chloride into cracked SHCC. -       The influence of low and high temperatures on SHCC durability performance. -       The mechanism of crack control reducing ASR and corrosion rate, and results on chloride-induced corrosion of embedded steel reinforcement. -       Self-healing of cracks in SHCC. -       A conceptual durability design framework for SHCC and R/SHCC structures andmembers.  .